The primary and secondary electrocaloric effect at ferroelectric-ferroelectric transitions in lead-free ceramics. (15th March 2020) - Wang, Haoyu; Zhang, Le; Sun, Yunlong; Cazorla, Claudio; Guo, Mengyao; Li, Ying; Lam, Kwok Ho; Lou, Xiaojie; Wang, Danyang
Abstract: Secondary electrocaloric effect (ECE) arising from piezoelectricity combined with crystal thermal expansion was often overlooked in ECE studies of ferroelectric ceramics. This work mainly evaluated the primary ECE (ΔTECE ) and secondary ECE (∆T2 ) of eco-friendly BaSn x Ti 1 - x O3 (BSnT100 x, 0 < x < 12%) ceramics near the tetragonal (T)-orthorhombic (O) transition. Intriguingly, a maximum overall ΔT 0.85 K was obtained at the T-O transition ( 300 K) of BSnT2 under an electric field of 2 kV/mm, with ∆TECE and ∆T2 amounting to 0.75 K, 0.1 K, respectively. This ECE result is 40% superior than the larger ECE reported previously for BSnT system. Graphical abstract: Image, graphical abstract